Using Reference Class Forecasting in Transport Infrastructure Projects - الشيخ دانا; عمران جمال; الأعرج مضر (Latakia University Journal -Engineering Sciences Series, 2023)
Transport infrastructure projects face the problem of increasing estimated costs, time delays, and diminishing future returns when implemented. These projects are characterized by a high investment value and a high degree of complexity, as well as facing political, economic and social risks (such as inflation, competition, new technology, lack of expertise), which makes them the focus of discussion and criticism at the local and international levels. This research sheds light on the poor performance of transport infrastructure projects, the root causes of this performance, and the proposed solutions to address the performance of these projects. The research proposes the adoption of the Reference Class Forecasting Framework, as it is one of the latest methods adopted to improve the performance of transport infrastructure projects at the global level. This framework is illustrated by providing a numerical example based on the data of 29 real-life projects. The research recommends the adoption of Reference Class Forecasting to improve the performance of transport infrastructure projects in the Arab countries, in line with the rest of the world. The research also indicates the importance of documenting the performance of these projects in the Arab countries in order to obtain good quality data. The research notes that this method does not guarantee obtaining accurate forecasts. It is capable of correcting project management decisions by determining the size of the expected cost and time overruns of the project under study, by comparing its forecast to the performance of previous projects; and by taking the necessary measures to address the causes leading to these overruns.